Biomimetic and hierarchical nerve conduits from multifunctional nanofibers for guided peripheral nerve regeneration. (November 2020) - Wang, Juan; Cheng, Yuan; Wang, Haoyu; Wang, Yuhao; Zhang, Kuihua; Fan, Cunyi; Wang, Hongjun; Mo, Xiumei
Abstract: Development of a functional nerve conduit to replace autografts remains a significant challenge particularly considering the compositional complexity and structural hierarchy of native peripheral nerves. In the present study, a multiscale strategy was adopted to fabricate 3D biomimetic nerve conduit from Antheraea pernyi silk fibroin ( Ap F)/(Poly(L-lactic acid-co-caprolactone)) (PLCL)/graphene oxide (GO) ( Ap F/PLCL/GO) nanofibers via nanofiber dispersion, template-molding, freeze-drying and crosslinking. The resultant conduits exhibit parallel multichannels (ϕ = 125 µm) surrounded by biomimetic fibrous fragments with tailored degradation rate and improved mechanical properties in comparison with the scaffold without GO. In vitro studies showed that such 3D biomimetic nerve scaffolds had the ability to offer an effective guiding interface for neuronal cell growth. Furthermore, these conduits showed a similarity to autografts in vivo repairing sciatic nerve defects based on a series of analysis (walking track, triceps weight, morphogenesis, vascularization, axonal regrowth and myelination). The conduits almost completely degraded within 12 weeks. These findings demonstrate that the 3D hierarchical nerve guidance conduit (NGC) with fascicle-like structure have great potential for peripheral nerve repair. Graphical abstract: Image, graphical abstract